ANALISIS PEMBANGUNAN SEKTOR KEUANGAN PADA SEKTOR JASA DI INDONESIA - Dini Hariyanti (Media Ekonomi, 2018)
Analyze how Financial Sector Development can affect the Service Sector in Indonesia using the Seemingly Unrelated Regression approach during the 2008-2015 period. This study uses quarterly data in the period 2008.1 - 2015.4. The year 2008 was taken as the beginning of observing the equation model because the period after the global crisis affected the global financial sector. The analysis tool used in this study uses a regression model with the SUR (Seemengly Unrelated Regression) approach. Using the existing model approach, it was concluded that the determinants of the gross national savings model in the service sector in Indonesia were influenced by the stock market index, gross domestic product, and real sector bank loans. The determinants of the banking credit model in the service sector in Indonesia are influenced by variables of the financial sector development index, stock market index, gross domestic product, service sector output, and gross national savings. While in the investment model equation, there are no variables that affect investment in the service sector. This is because there is a time lag in determining investment. Finally, the determinants of the output model in the service sector in Indonesia as well as the banking sector credit equation are influenced by the variables of the banking sector development index, stock market index, gross domestic product, service sector output, and gross national savings.